Boron nitride nanotubes as carriers of genistein for multitherapeutic cancer treatment: A DFT study of electronic and solubility properties - Mashhoun, Sara; Tavahodi, Ali (Frontiers in Nanotechnology, 2024)
Increasing cancer mortality statistics demand more accurate and efficient treatments. Nanostructures have proved to be promising choices in this regard. Nanotubes with large surface areas can play multiple roles from drug carriers in targeted drug delivery to beam absorbers in the photothermal method. While carbon nanotubes (CNTs) show cytotoxicity, Boron Nitride Nanotubes offer wide bandgap and biocompatibility. In this study, we investigate the electronic and solvation properties of (5,5), (6,6), and (7,7) BNNTs computationally by the density functional theory. For multimodal therapy, we considered Iron (Fe) doping in the BNNT, which can be helpful in hyperthermia due to the magnetic moment of Fe. Our results show that doping has improved the band positions. Furthermore, we implemented an organic anticancer molecule, genistein, a metastasis inhibitor. All potent configurations connecting genistein with BNNT covalently demonstrated enhanced water solubility as compared to pristine and Fe-doped BNNTs. The results suggest that the (7,7) C3 complex is the most stable structure and the best drug carrier.